Evaluasi Pembinaan Prestasi Tenis Lapangan Klub Tumou Tou Tenis Academi Kabupaten Minahasa Provinsi Sulawesi Utara - Mokoagow, Muhammad Sujiran; Priyono Sulaiman, Bambang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to evaluate the performance development in the Tumou Tou Academic Tennis Club. This research uses a qualitative approach with the CIPP Evaluation model (Context Input Process Product) developed by Stuffbem. The subjects of this research are the managers, coaches, athletes, and parents. With data collection using observation, interviews, and documentation. The research results show: the context of the background, vision, mission, and program objectives are good; the input of human resources (Administrators, Coaches, Athletes) is adjusted and placed according to their fields, the availability of facilities in terms of the field is insufficient with 25 athletes, with the time already set and still lacking funding sources from each athlete's parents; the training program process is scheduled with directly appointed coaches and the acceptance of athletes at any time. coordination that runs well; product achievements and welfare in the medium category with stable achievements and welfare categorized by championship results. Conclusion, that the achievement development in the Tumou Tou Tennis Academic Club is already good in terms of vision and mission context, human resource availability input, coach recruitment system, and facilities and infrastructure. Keywords: evaluation, achievement coaching, tennis,